(NwOZDU[NYJ KORABLX (B:s (NLITERATURNYE BALLADY (B: (NPEREWODY (B/s - (NmURIK(B, (Na(B. (Ng(B.,s; (NpARIN(B, (Na(B. (Nw(B.,s; (NeROFEEW(B, (Nw(B. (Nw(B.,s; (NgALAHOWA(B, (Nn(B. (Na(B.,s; (NwEJLERT(B, (Nr(B. (Nr(B.,s ((NmOSKWA (B:s (NpRAWDA(B,s, 1986)
(Nl)QÆTERATURNO@ BALADO@(B, (NZASNOWANO@ NA FOLXKLORNÆJ TRADICÆÇ(B, (NZAHOPL@WALISQ gETE TA {ILLER(B, (NwALXTER sKOTT TA pETEFÆ(B, (NvUKOWSXKIJ TA bLOK(B.s)E
(NoRIG)QÆNAL ZAPISU ZA POSILANNQMs)E
Keywords: (NhUDOVNQ L)QÆTERATURAs)E -- (NpOEZ)QÆQs)E -- (NbALADIs